Christopher Gluck: 1714-1787 - Unknown:::Creator::::::::::::; Perry, Eugene A. (Eugene Ashton), 1864-1948 (publisher):::Contributor:::::::::::: (Malden, Massachusetts; Eugene A. Perry; United States)
Portrait of Christoph Willibald Gluck.